Identification and risk mitigation strategy of cocoa commodities supply chain using fuzzy house of risk method (Fuzzy-HOR) - Santoso, Imam; Nazwanuril Wafi, Noval (International Journal of Engineering and Technology, 2019)
Supply Chain Management should be considered in a business entity as it relates to the process of managing the flow of goods from upstream to downstream. The supply chain process involves multiple parties, in which each of the parties involved may pose a supply chain risk so that supply chain risk management is required to manage supply chain activities. PT. XYZ as the research place is located in Blitar, East Java which is one of the business entities engaged in cocoa commodities. Currently, PT. XYZ has not had a structured supply chain risk management yet to identify and mitigate risks. This study aims to identify supply chain risk and determine risk mitigation strategies that need to be applied. The method used was Fuzzy-HOR. This study involved expert respondents consisting of cocoa farmers and employees (production managers and operational managers). The result of risk identification found 11 risks on farmerâ€™s activity which was composed of 15 risk agents. Next, 19 risks were found on companyâ€™s activity which was consisted of 25 risk agents. Calculation results using Fuzzy-HOR on phase 1 resulted in 9 risk agents on farmerâ€™s activity and 18 risk agents on companyâ€™s activity that required mitigation strategies design. In Fuzzy-HOR phase 2, there were 17 farmerâ€™s mitigation strategies and 30 companyâ€™s mitigation strategies.Â Â